2021
DOI: 10.3390/jpm11030228
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Attachment and Gambling in Adolescence: A Multiple Mediation Analysis with Developmental Perspective, Theory of Mind (Friend) and Adaptive Response

Abstract: Introduction: Several studies have supported the evidence that attachment styles are a central factor in adolescent gambling problems. On this theoretical basis, the aim of the present study is to analyze a hypothesized mediation model exploring both the direct and indirect effects of insecure attachment on gambling disorder by investigating the role of the developmental perspective, theory of mind (friend) and adaptive response in that relationship. Method: The sample consists of 178 adolescents who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
3
9
0
1
Order By: Relevance
“… Horak et al (2021) found evidence that childhood trauma represented a significant predictor of a diagnosis of gambling disorder, in agreement with the suggestions of others ( Felsher et al, 2010 ; Schwaninger et al, 2017 ). In line with our proposal ( vide supra ), the (childhood) trauma decreased here also the capabilities of attachment drives to release β-endorphin, because the onset of insecure attachment predicted the symptomatic expression of pathological gambling among adolescents ( Magoon and Ingersoll, 2006 ; Terrone et al, 2021 ). It should be noted that other essential drives, for example, the hunger drive ( Black et al, 2013 ) and the sexual drive ( Grant and Steinberg, 2005 ; Cowie et al, 2019 ), are additionally often corrupted in patients suffering from gambling disorder.…”
Section: Rationalesupporting
confidence: 88%
“… Horak et al (2021) found evidence that childhood trauma represented a significant predictor of a diagnosis of gambling disorder, in agreement with the suggestions of others ( Felsher et al, 2010 ; Schwaninger et al, 2017 ). In line with our proposal ( vide supra ), the (childhood) trauma decreased here also the capabilities of attachment drives to release β-endorphin, because the onset of insecure attachment predicted the symptomatic expression of pathological gambling among adolescents ( Magoon and Ingersoll, 2006 ; Terrone et al, 2021 ). It should be noted that other essential drives, for example, the hunger drive ( Black et al, 2013 ) and the sexual drive ( Grant and Steinberg, 2005 ; Cowie et al, 2019 ), are additionally often corrupted in patients suffering from gambling disorder.…”
Section: Rationalesupporting
confidence: 88%
“…The two studies that adopted a trait model of attachment (Pace et al, 2013;Terrone et al, 2021) found a positive association between insecure attachment and gambling. In particular, Pace et al (2013) found that at-risk and pathological gamblers reported higher level of fearful attachment style compared to non-gamblers, and at-risk gamblers also reported lower levels of secure attachment style compared to non-gamblers.…”
Section: Adolescents and Young Adults Trait Model Of Attachment And G...mentioning
confidence: 99%
“…Se ha comprobado que las experiencias tempranas negativas con las figuras de apego, como son los abusos emocionales desencadenarían el establecimiento de un estilo de apego inseguro que se mantendría estable hasta la edad adulta y conducirían al desarrollo de la desesperanza (Gaskin-Wasson et al, 2017;Miniati et al, 2017). En cuanto a su relación con el trastorno de juego, varios estudios han apoyado la evidencia de que los estilos de apego son un factor central en los trastornos de juego de los adolescentes (Terrone et al, 2021). Concretamente, el 70% de las personas con un trastorno de juego presentan un estilo de apego inseguro (Di Trani, et al, 2017).…”
Section: Introductionunclassified